Resultados de las encuestas realizadas a los egresados del departamento de física durante los años 2005 y 2006 - Cardona, Javier; Ibagón, Carolina; Martínez, Julián (MOMENTO, 2005)
During the second semester of 2005, a poll to gather information about the alumni of our department was designed and applied. This article describes how the polls were done and it also presents the most relevant results.